Karakterisasi Komposit Selulosa Bakteri – Ekstrak Daun Kacapiring (Gardenia Jassminoides J.Ellis) dengan Penambahan Crosslinker - Muhammad Iqbal; Elsa Yuniarti; Ali Amran; Ananda Putra (Jurnal Periodic Jurusan Kimia UNP, 2022)
Bacterial cellulose (BC) can be applied in various fields such as biomedical, separation membranes, artificial blood vessels, and substrates for cartilage tissue engineering. Bacterial cellulose still has low mechanical properties, so a bacterial cellulose composite was formed with Gardenia Leaf Extract (CBC-GLE) to obtain higher mechanical properties. The purpose of this study was to determine the effect of adding crosslinker starch 1,2 and 3% soaked with CBC-GLE to form (CBC-GLEC) by knowing the mechanical, physical, and structural properties of (CBC-GLEC). Bacterial cellulose is produced from a mixture of coconut water, sugar and urea. Then fermented with Acetobacter Xylinum for 14 days. Bacterial cellulose was composited with gardenia leaf extract and was called the bacterial cellulose-gardenia leaf extract composite (CBC-GLE). BC, CBC-GLE and CBC-GLEC were characterized by testing water content, tensile strength, compressive strength, structural analysis using FTIR and degree of crystallinity using XRD. The addition of Crosslinker can reduce the percentage of water content of CBC-GLEC 3% with a value of 90.73%, CBC-GLE 95.69% and BC 99.21%. The best tensile strength test results were the addition of crosslinked amilum starch with a concentration of 3% (CBC-GLEC) with a value of 121.45 MPa, CBC-GLE 49.81 MPa and BC 32.09 MPa. The best compressive strength test results were the addition of starch crosslinker with a concentration of 3% (CBC-GLEC) with a value of 4.38 mm, CBC-GLE 3.42 mm and BC 2.65 mm. The results of the FTIR spectrum showed that the functional groups contained in cellulose only experienced a shift, while the results of the analysis of the degree of crystallinity showed that the percentage of the degree of crystallinity of BC was 75.47%, CBC-GLE 94.42 %, CBC-GLEC starch 3% was 67.26 %